2016
DOI: 10.4049/jimmunol.1501416
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splice Transcripts for MHC Class I–like MICA Encode Novel NKG2D Ligands with Agonist or Antagonist Functions

Abstract: MHC class I chain–related proteins A and B (MICA and MICB) and UL16-binding proteins are ligands of the activating NKG2D receptor involved in cancer and immune surveillance of infection. Structurally, MICA/B proteins contain an α3 domain, whereas UL16-binding proteins do not. We identified novel alternative splice transcripts for MICA encoding five novel MICA isoforms: MICA-A, -B1, -B2, -C, and -D. Alternative splicing associates with MICA*015 and *017 and results from a point deletion (G) in the 5′ splice don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In particular, Gowen et al have shown that the RNA-binding protein (RBP) RBM4 supports ULBP1 expression by suppressing a novel alternatively spliced isoform of ULBP1 mRNA and appears to be specific for the differential splicing of ULBP1 but not of other NKG2D ligands ( 32 ). Although alternative splicing isoforms have been described for MICA ( 68 ), ULBP4 ( 69 ) and ULBP5 ( 70 ), the molecular mechanisms involved in their regulation is still unknown.…”
Section: Rna Splicingmentioning
confidence: 99%
“…In particular, Gowen et al have shown that the RNA-binding protein (RBP) RBM4 supports ULBP1 expression by suppressing a novel alternatively spliced isoform of ULBP1 mRNA and appears to be specific for the differential splicing of ULBP1 but not of other NKG2D ligands ( 32 ). Although alternative splicing isoforms have been described for MICA ( 68 ), ULBP4 ( 69 ) and ULBP5 ( 70 ), the molecular mechanisms involved in their regulation is still unknown.…”
Section: Rna Splicingmentioning
confidence: 99%
“…Moreover, numerous MICA splice variants have been documented thus far (Figure 1C), with the majority binding NKG2D similarly as their wildtype counterparts, highlighting that lack of a domain (e.g. a3 domain) does not necessarily reduce binding affinity (60). Interestingly, there is a naturally occurring MICA-MICB null combination (deletion of MICA and premature stop codon for MICB) that exists on the HLA-B48 haplotype found in East Asian and South American populations (72)(73)(74).…”
Section: Mica and Micbmentioning
confidence: 93%
“…It is also worth noting that NKG2D-L differ in their affinity (K D ) and avidity for NKG2D, such that ULBP1 (the only ULBP member tested to date) has the highest affinity (1.1 mM), followed by MICA (0.9-1 mM) and MICB (800 nM) (55)(56)(57)(58)(59). Therefore, it is speculated that NKG2D may transduce different signals or activate separate downstream pathways based on which ligand or allelic variant is bound (60), which supports the various functions of NKG2D discussed prior. Surprisingly, the role of NKG2D-L extends beyond providing a signal for cellular stress.…”
Section: The Nkg2d Receptor-ligand Axis Plays An Important Role In Immune Recognitionmentioning
confidence: 99%